European Mediation and Indigenous Mediation - Brandão Bárrios, Luísa (Teisė, 2020)
The article investigates the European and Indigenous mediation and its different circumstances. Mediation is one of a variety of procedures to solve a conflict; it is based on the voluntary participation of the parties and it is a procedure, in which an intermediary without adjudicatory powers (the mediator) systematically facilitates communication between the parties with the aim of enabling the parties themselves to take responsibility for resolving their dispute.
Keywords: alternative dispute resolution; mediation; mediator